Pengaruh Penerapan Pendekatan Realistic Mathematics Education Terhadap Kemampuan Penalaran Matematis Peserta Didik Di Kelas XII IPA SMA Pertiwi 1 Padang - NURHAFIZAH . (Jurnal Edukasi dan Penelitian Matematika, 2019)
The mathematics reasoning abilities is one of the abilities that should be had by every students in mathematics learning. However, in class XII IPA SMA Pertiwi 1 Padang, this ability is still low. One effort that can be done to improve students' mathematical reasoning ability is to apply the Realistic Mathematics Education (RME) approach. The purpose of this study is to describe the increase in reasoning ability of students who learn with the RME approach and describe whether the improvement ability of students who learn with the RME approach is better than the reasoning ability of students who learn with conventional learning in class XII IPA SMA Pertiwi 1 Padang. The type of this research is a quasi-experiment and descriptive research design with Randomize Control Group Only Design. The research instrument was LKPD and reasoning ability test. Based on the results of the training analysis on LKPD, it was found that the development of reasoning ability increased with the RME approach, and based on the results of the test analysis it was found that the reasoning ability of students who learned the RME approach was better than the reasoning ability of students who studied with conventional learning in class XII IPA Pertiwi 1 Padang.Key Words – The Ability Of Mathematical Reasoning, Realistisc Mathematics Education, Learning Conventional.